Lulus Tepat Waktu Mahasiswa Akuntansi: Faktor Apa Saja Yang Mempengaruhi - Hayu Wikan Kinasih; Agung Prajanto; Mila Sartika (Juara: Jurnal Riset Akuntansi, 2022)
For most of universities in Indonesia, student graduation is determined by thesis. Some student considered that thesis is a stressor that causes their laziness. Assumption that thesis is a stressor impact on student graduation timeliness. Student graduation timeliness is one indicator that determined the universities quality. There are some factors affecting student graduation timeliness, including the role of supervisor, student activity, guidance media, and the number of guidance activity. This study aims to analyze factors affecting student graduation timeliness majoring in accounting of X University. Binary logistic analysis is used in examining the dependency relation between student graduation timeliness and factors that affecting. The result show that variabel student activity affected on student graduation timeliness. Variable the role of supervisor, guidance media, and the number of guidance activity has no effect on student graduation timeliness.